Organization of the Educational Process on the Basis of Cooperative Pedagogy Theoretical And Methodological Foundations of Education - I.R.Radjabova (Zien Journals, 2023)
In today's conditions, where the speed of information flow has increased beyond imagination due to the development of science and technology, it is necessary to turn students into the subjects of the educational process, to solve their educational problems independently, and to apply them to the national educational system based on the pedagogy of cooperation. The article is dedicated to showing methodological and theoretical aspects of this.
Keywords: showing; theoretical; speed; system